For the sets A, B, C and D, we have-
Property 1: A×(B∪C)=(A×B)∪(A×C)
Proof:
Let (x,y)∈A×(B∪C)
⇔x∈A,y∈(B∪C)
⇔x∈A,(y∈B or y∈C)
⇔(x∈A,y∈B) or (x∈A,y∈C)
⇔(x,y)∈A×B or (x,y)∈A×C
⇔(x,y)∈(A×B)∪(A×C)
⸫ A×(B∪C)=(A×B)∪(A×C)
Property 2: A×(B∩C)=(A×B)∩(A×C)
Proof:
Let (x,y)∈A×(B∩C)
⇔x∈A,y∈(B∩C)
⇔x∈A,(y∈B and y∈C)
⇔(x∈A,y∈B) and (x∈A,y∈C)
⇔(x,y)∈A×B and (x,y)∈A×C
⇔(x,y)∈(A×B)∩(A×C)
⸫ A×(B∩C)=(A×B)∩(A×C)
Property 3: (A×B)∪(C×D)=(A∪C)×(B∪D)
Proof:
Let (x,y)∈(A×B)∪(C×D)
⇔(x,y)∈(A×B) or (x,y)∈(C×D)
⇔(x∈A,y∈B) or (x∈C,y∈D)
⇔(x∈A or x∈C), (y∈B or y∈D)
⇔(x∈A∪C), (y∈B∪D)
⇔(x,y)∈(A∪C)×(B∪D)
⸫ (A×B)∪(C×D)=(A∪C)×(B∪D)
Property 4: (A×B)∩(C×D)=(A∩C)×(B∩D)
Proof:
Let (x,y)∈(A×B)∩(C×D)
⇔(x,y)∈(A×B) and (x,y)∈(C×D)
⇔(x∈A and x∈C) and (y∈B and y∈D)
⇔(x∈A∩C) and (y∈B∩D)
⇔(x,y)∈(A∩C)×(B∩D)
⸫ (A×B)∩(C×D)=(A∩C)×(B∩D)
Property 5: A×(B−C)=(A×B)−(A×C)
Proof:
Let (x,y)∈A×(B−C)
⇔x∈A and y∈(B−C)
⇔x∈A and (y∈B and y∉C)
⇔(x∈A and y∈B) and (x∈A and y∉C)
⇔(x,y)∈A×B and (x,y)∉A×C
⇔(x,y)∈(A×B)−(A×C)
⸫ A×(B−C)=(A×B)−(A×C)
Property 6: (A−B)×C=(A×C)−(B×C)
Proof:
Let x∈(A−B)×C
⇔x∈(A−B) and y∈C
⇔(x∈A and x∉B) and y∈C
⇔(x∈A and y∈C) and (x∉B and y∈C)
⇔(x,y)∈A×C and (x,y)∉B×C
⇔(x,y)∈(A×C)−(B×C)
⸫ (A−B)×C=(A×C)−(B×C)
Property 7: A×B=B×A iff A=ϕ or B=ϕ or A=B
Proof:
Case 1:
Let A=ϕ
Now A×B=ϕ×B=ϕ [⸪ A=ϕ ]
also B×A=B×ϕ=ϕ [⸪ A=ϕ ]
Hence A×B=B×A
Case 2:
Let B=ϕ
Now A×B=A×ϕ=ϕ [⸪ B=ϕ]
also B×A=ϕ×A=ϕ [⸪ B=ϕ]
Hence A×B=B×A
Case 3:
Let A=B
Now A×B=A×A [⸪ A=B ]
also B×A=A×A [⸪ A=B ]
Hence A×B=B×A
Q. If A×B=B×A then show that A=B
Solution:
Let a∈A⇒(a,b)∈A×B ∀ b∈B
⇒(a,b)∈B×A [⸪ A×B=B×A]
⇒a∈B [definition of Cartesian product of sets]
Conversely,
Let b∈A⇒(a,b)∈A×B ∀ a∈A
⇒(a,b)∈B×A [⸪ A×B=B×A]
⇒b∈A [definition of Cartesian product of sets]
Hence, A=B
Q. If A×B=A×C then show that B=C
Solution:
Let b∈B⇒(a,b)∈A×B ∀ a∈A
⇒(a,b)∈A×C [⸪ A×B=A×C]
⇒b∈C [definition of Cartesian product of sets]
Conversely,
Let c∈C⇒(a,c)∈A×C ∀ a∈A
⇒(a,c)∈A×B [⸪ A×B=A×C]
⇒c∈B [definition of Cartesian product of sets]
Hence, B=C
Q. If A, B and C be three sets where B⊆A then show that (B×C)⊆(A×C)
Solution:
Let (b,c)∈B×C
⇒b∈B and c∈C
⇒b∈A and c∈C [⸪ B⊆A]
⇒(b,c)∈A×C
Hence (B×C)⊆(A×C)
Q. If A, B and C be three sets where A⊆B then show that (A×C)⊆(B×C)
Solution:
Let (a,c)∈A×C
⇒a∈A and c∈C
⇒a∈B and c∈C [⸪ A⊆B]
⇒(a,c)∈B×C
Hence (A×C)⊆(B×C)
Q. If A⊆B and C⊆D then show that (A×C)⊆(B×D)
Solution:
Let (a,c)∈A×C
⇒a∈A and c∈C
⇒a∈B and c∈D [⸪ A⊆B and C⊆D]
⇒(a,c)∈B×D
Hence (A×C)⊆(B×D)
Property 1: A×(B∪C)=(A×B)∪(A×C)
Proof:
Let (x,y)∈A×(B∪C)
⇔x∈A,y∈(B∪C)
⇔x∈A,(y∈B or y∈C)
⇔(x∈A,y∈B) or (x∈A,y∈C)
⇔(x,y)∈A×B or (x,y)∈A×C
⇔(x,y)∈(A×B)∪(A×C)
⸫ A×(B∪C)=(A×B)∪(A×C)
Property 2: A×(B∩C)=(A×B)∩(A×C)
Proof:
Let (x,y)∈A×(B∩C)
⇔x∈A,y∈(B∩C)
⇔x∈A,(y∈B and y∈C)
⇔(x∈A,y∈B) and (x∈A,y∈C)
⇔(x,y)∈A×B and (x,y)∈A×C
⇔(x,y)∈(A×B)∩(A×C)
⸫ A×(B∩C)=(A×B)∩(A×C)
Property 3: (A×B)∪(C×D)=(A∪C)×(B∪D)
Proof:
Let (x,y)∈(A×B)∪(C×D)
⇔(x,y)∈(A×B) or (x,y)∈(C×D)
⇔(x∈A,y∈B) or (x∈C,y∈D)
⇔(x∈A or x∈C), (y∈B or y∈D)
⇔(x∈A∪C), (y∈B∪D)
⇔(x,y)∈(A∪C)×(B∪D)
⸫ (A×B)∪(C×D)=(A∪C)×(B∪D)
Property 4: (A×B)∩(C×D)=(A∩C)×(B∩D)
Proof:
Let (x,y)∈(A×B)∩(C×D)
⇔(x,y)∈(A×B) and (x,y)∈(C×D)
⇔(x∈A and x∈C) and (y∈B and y∈D)
⇔(x∈A∩C) and (y∈B∩D)
⇔(x,y)∈(A∩C)×(B∩D)
⸫ (A×B)∩(C×D)=(A∩C)×(B∩D)
Property 5: A×(B−C)=(A×B)−(A×C)
Proof:
Let (x,y)∈A×(B−C)
⇔x∈A and y∈(B−C)
⇔x∈A and (y∈B and y∉C)
⇔(x∈A and y∈B) and (x∈A and y∉C)
⇔(x,y)∈A×B and (x,y)∉A×C
⇔(x,y)∈(A×B)−(A×C)
⸫ A×(B−C)=(A×B)−(A×C)
Property 6: (A−B)×C=(A×C)−(B×C)
Proof:
Let x∈(A−B)×C
⇔x∈(A−B) and y∈C
⇔(x∈A and x∉B) and y∈C
⇔(x∈A and y∈C) and (x∉B and y∈C)
⇔(x,y)∈A×C and (x,y)∉B×C
⇔(x,y)∈(A×C)−(B×C)
⸫ (A−B)×C=(A×C)−(B×C)
Property 7: A×B=B×A iff A=ϕ or B=ϕ or A=B
Proof:
Case 1:
Let A=ϕ
Now A×B=ϕ×B=ϕ [⸪ A=ϕ ]
also B×A=B×ϕ=ϕ [⸪ A=ϕ ]
Hence A×B=B×A
Case 2:
Let B=ϕ
Now A×B=A×ϕ=ϕ [⸪ B=ϕ]
also B×A=ϕ×A=ϕ [⸪ B=ϕ]
Hence A×B=B×A
Case 3:
Let A=B
Now A×B=A×A [⸪ A=B ]
also B×A=A×A [⸪ A=B ]
Hence A×B=B×A
Q. If A×B=B×A then show that A=B
Solution:
Let a∈A⇒(a,b)∈A×B ∀ b∈B
⇒(a,b)∈B×A [⸪ A×B=B×A]
⇒a∈B [definition of Cartesian product of sets]
Conversely,
Let b∈A⇒(a,b)∈A×B ∀ a∈A
⇒(a,b)∈B×A [⸪ A×B=B×A]
⇒b∈A [definition of Cartesian product of sets]
Hence, A=B
Q. If A×B=A×C then show that B=C
Solution:
Let b∈B⇒(a,b)∈A×B ∀ a∈A
⇒(a,b)∈A×C [⸪ A×B=A×C]
⇒b∈C [definition of Cartesian product of sets]
Conversely,
Let c∈C⇒(a,c)∈A×C ∀ a∈A
⇒(a,c)∈A×B [⸪ A×B=A×C]
⇒c∈B [definition of Cartesian product of sets]
Hence, B=C
Q. If A, B and C be three sets where B⊆A then show that (B×C)⊆(A×C)
Solution:
Let (b,c)∈B×C
⇒b∈B and c∈C
⇒b∈A and c∈C [⸪ B⊆A]
⇒(b,c)∈A×C
Hence (B×C)⊆(A×C)
Q. If A, B and C be three sets where A⊆B then show that (A×C)⊆(B×C)
Solution:
Let (a,c)∈A×C
⇒a∈A and c∈C
⇒a∈B and c∈C [⸪ A⊆B]
⇒(a,c)∈B×C
Hence (A×C)⊆(B×C)
Q. If A⊆B and C⊆D then show that (A×C)⊆(B×D)
Solution:
Let (a,c)∈A×C
⇒a∈A and c∈C
⇒a∈B and c∈D [⸪ A⊆B and C⊆D]
⇒(a,c)∈B×D
Hence (A×C)⊆(B×D)
Post a Comment